(untitled) (Medico Legal Update, 2021)
Background: Street traffic accidents were a main community healthiness problematic particularly in low and middle-income countries, head injuries were found to be the most common injuries. Objectives: to identify the relationship of road traffic injuries with different associated factors. Methodology: This was a cross sectional study conducted on 500 Road Traffic Accidents victims admitted to the emergency unit at Al-Sader Teaching General Hospital in Al Najaf Holy province- Iraq. Data collection was done using a pretested questionnaire. A medical team including neurosurgeon, medical, and orthopedics to identify the types (pattern) of cranio-cerebral injuries evaluated outcomes of the injury cases. Results: Most of the victims are males in their productive age, motorcycle is the most common cause of accidents, head injuries constituted the highest proportion (39.6%), the mortality rate was (13.6%), and unhealthy behaviors during driving were dominated. Conclusion: Cerebral contusions and skull fractures were the most common lesions among head injuries and trauma brain injuries victims.